2023
DOI: 10.1152/jn.00459.2022
|View full text |Cite
|
Sign up to set email alerts
|

Electrocorticography reveals the dynamics of famous voice responses in human fusiform gyrus

Abstract: Voice and face processing occur through convergent neural systems that facilitate speaker recognition. Neuroimaging studies suggest that familiar voice processing engages early visual cortex, including the bilateral fusiform gyri (FG) on the basal temporal lobe. However, what role the FG plays in familiar voice processing and whether it is driven by bottom-up or top-down mechanisms is unresolved. In this study we directly examined neural responses to familiar voices and faces in human FG using direct cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…This time window thus delineates when we can expect to find evidence for representations of different person characteristics in the RSA. This time course of voice decoding is similar to time courses that have been reported for general sound decoding ( 32 , 46 ), the time courses reported for the decoding of visual stimuli ( 33 , 47 ), as well as the time courses of neural responses to famous faces established via electrocorticographical recordings ( 48 ).…”
Section: Resultssupporting
confidence: 84%
“…This time window thus delineates when we can expect to find evidence for representations of different person characteristics in the RSA. This time course of voice decoding is similar to time courses that have been reported for general sound decoding ( 32 , 46 ), the time courses reported for the decoding of visual stimuli ( 33 , 47 ), as well as the time courses of neural responses to famous faces established via electrocorticographical recordings ( 48 ).…”
Section: Resultssupporting
confidence: 84%
“…As a result, the time window also delineates when we can expect to find evidence for representations of different person characteristics in the RSA analysis. These temporal dynamics of voice decoding are similar to temporal dynamics that have been reported for general sound decoding (Lowe et al, 2018, Lowe et al, 2021, the temporal dynamics reported for the decoding of visual stimuli (Cichy et al, 2018, Dobs et al, 2019, as well as the temporal dynamics of neural responses to famous faces established via electrocorticographical recordings (Rhone et al, 2023).…”
Section: Different Voice Recordings Can Be Distinguished In the Brain...supporting
confidence: 81%
“…While the source localization of the present voice-induced N250 in fusiform gyrus in young healthy adults potentially represents a novel finding for scalp-recorded EEG, it may be noted that our findings can be related to a very recent study using intracranial EEG recordings from epilepsy patients, in which the authors directly demonstrated an electrophysiological response in fusiform cortex in response to famous voices, with onset latencies close to 300 ms [ 79 ]. Although more research is necessary to delineate in more detail the contribution of fusiform cortex to voice learning, the present findings support the notion of an early perceptual interaction in areas implicated in voice and face processing [ 2 , 7 ] (see also [ 80 ]).…”
Section: Discussionmentioning
confidence: 52%